Accumulation of NH4+ and NO3− inside Biofilms of Natural Microbial Consortia: Implication on Nutrients Seasonal Dynamic in Aquatic Ecosystems - Andi Kurniawan; Tatsuya Yamamoto (International Journal of Microbiology)
Microbial biofilms are ubiquitous in aquatic ecosystems. Inside the biofilm is the nutrient-rich microenvironment promoted by the accumulation of the nutrient ions such as NH4+ and NO3− from surrounding water. The present study investigated the characteristics of NH4+ and NO3− accumulation into the biofilm of natural microbial consortia collected from Lake Biwa, Japan. The results showed the following: (1) the concentrations of NH4+ and NO3− inside the biofilm were much higher than those in the surrounding water; (2) the nutrient ion concentration inside the biofilm changed in synchrony with those in the surrounding water; (3) biofilm polymers have both positively and negatively charged sites; (4) electrostatic attractive interactions between the charged sites on biofilm polymers and oppositely charged ions outside the biofilm seem to play important roles in the accumulation of nutrient ions into the biofilm from the surrounding water; (5) the bacterial community structure differs between the biofilm and surrounding water. The present study revealed that the accumulation of nutrient ions into the biofilm indicates the removal of these ions from water outside the biofilm. According to the result of this study, accumulation of ions such as NH4+ and NO3− into the biofilm of natural microbial consortia may have implications on nutrients seasonal dynamic in aquatic ecosystems.